Impact of Foreign Debt on Economic Growth: Evidence from Pakistan - Rauf, Abdur; Khan, Amara Akram (Asian Economic and Financial Review, 2017)
This study analyzes the impact of foreign debt on economic growth of Pakistan, using annual time series data from1972 to 2013. The research question is tested through ARDL econometric framework and the estimated result shows that foreign debt exerts significant negative impact on economic growth which confirms the existences of debt overhang in Pakistan. Both physical and human capital has strong association with economic growth of Pakistan. The coefficient of Error Correction Term (ECT) suggested that any deviation from the long term inequality is corrected by a moderate speed over each year. Significant ECT is further proof of the existence of stable long run relationship. It can be suggested that the proper management of debt may help the government in attaining the desirable growth of the economy.